IMPLEMENTATION OF LEAN MANUFACTURING IN SMALL AND MEDIUM ENTERPRISES: EVIDENCE FROM UZBEKISTAN - Abduraxmanova Fotima Odilbayevna (Modern American Journals, 2026)
Small and medium enterprises (SMEs) play a critical role in economic development, particularly in emerging economies. Despite the widely recognized benefits of Lean Manufacturing (LM), its adoption among SMEs remains limited and uneven. This study examines the level of awareness, implementation barriers, success factors, and performance outcomes of LM practices in manufacturing SMEs in Uzbekistan. A quantitative research design was employed, and primary data were collected through a structured questionnaire survey of 100 SMEs that have implemented or attempted to implement lean practices. The findings reveal that SMEs predominantly apply basic lean tools such as 5S, Kaizen, and standardized work, while advanced lean techniques remain underutilized. Key barriers include limited lean knowledge, resistance to change, and reliance on traditional management systems. Nevertheless, firms that successfully implemented LM reported significant improvements in productivity, quality, cost reduction, and waste elimination. The study provides empirical evidence from an under-researched transition economy and offers practical insights for SME managers and policymakers seeking to enhance competitiveness through lean practices.
Keywords: Lean Manufacturing, SMEs, Operational Performance, Continuous Improvement, Uzbekistan.